Multiple Kinases Can Phosphorylate the N-Terminal Sequences of Mitochondrial Proteins in Arabidopsis thaliana - Law, Yee-Song; Ngan, Ling; Yan, Junran; Kwok, Lok Y.; Sun, Yuzhe; Cheng, Shifeng; Schwenkert, Serena; Lim, Boon L. (Frontiers in Plant Science, 2018)
Phosphorylation of the transit peptides of nuclear-encoded preprotein is a well-known regulatory process of protein import in plant chloroplasts. In the Arabidopsis Protein Phosphorylation Site Database, 103 out of 802 mitochondrial proteins were found to contain one or more experimentally-proven phosphorylation sites in their first 60 amino acid residues. Analysis of the N-terminal sequences of selected mitochondrial preproteins and their homologs from 64 plant species showed high conservation among phosphorylation sites. The ability of kinases from various sources including leaf extract (LE), root extract (RE), wheat germ lysate (WGL) and STY kinases to phosphorylate N-terminal sequences of several respiratory chain proteins were examined by in vitro kinase assays. The three STY kinases were shown to phosphorylate the N-terminal sequences of some proteins we tested but exhibited different specificities. Interestingly, the N-terminal sequences of two mitochondrial ATP synthase beta subunit 1/3 (pF1β-1/3) could be phosphorylated by LE and RE but not by STY kinases, suggesting that there are uncharacterized presequence-phosphorylating kinases other than STY kinases present in RE and LE. Mitochondrial import studies showed that the import of RRL-synthesized pF1βs was impeded by the treatment of LE, and the addition of a short SSU transit peptide containing a phosphorylatable 14-3-3 binding site could enhance the import of LE-treated pF1βs. Our results suggested that the transit peptide of pSSU can compete with the presequences of pF1βs for an uncharacterized kinase(s) in leaf. Altogether, our data showed that phosphorylation of transit peptides/presequences are not uncommon for chloroplast-targeted and mitochondria-targeted proteins, albeit possibly differentially regulated.